Construction of Financial Technology in Banking Systems in Indonesia - Upik Mutiara; Lupita Risma Candanni; Rahmad Ramadhan Hasibuan (Universitas Ahmad Dahlan, 2019)
Introduction to The Problem: The use of information technology innovations in banking today through digital platforms or online or known as financial technology (commonly abbreviated as fintech) can indeed provide financial services to the public at a lower cost than traditional banking methods. But behind the sophistication of technology as well as an increase in banking risk, especially if the regulations that govern it have not been comprehensive.Purpose/Objective Study: This paper examines the development of various regulatory regulations in the field of fintech in Indonesia.Design/Methodology/Approach: The research method used in this study is qualitative through normative legal research. The obtained data analyzed by statutory approach to interpret the existing legal rules on Indonesian Banking.Findings: The results obtained are that the existence of fintech which is considered as disruptive innovation (disruptive innovation) has changed the old market and revolutionized the workings of traditional financial institutions. Therefore, the government through the financial authority that is authorized to respond to the development of fintech in the Indonesian banking system by making various regulations. In addition, the development of fintech business integration with banking institutions must also be a concern for both parties so that the development of fintech is not only a disruption but can also be a safe innovation for customers to use.Paper Type: Research Article